2011
DOI: 10.1002/ejic.201001101
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the [FeFe]‐Hydrogenase Maturase HydG

Abstract: International audienceRecent work conducted in several laboratories has shown that the [FeFe]-hydrogenase maturase HydG synthesizes both CO and CN– from tyrosine. We have very recently found that although CN– synthesis does not need the [4Fe-4S] cluster found in the HydG C-terminal domain, CO synthesis does require it. We have also proposed that the +H2N·–CH2–CO2– radical is a precursor for these two active site ligands. Here, we have extended our characterization of both the wild-type enzyme and a ThiH-like H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 37 publications
6
31
1
1
Order By: Relevance
“…S2), HydG variants lacking a functional second cluster are expected to produce − :CO 2 H-derived formate instead of CO and water. Points (i)-(iii) have already been addressed (11)(12)(13)26) and (ii) and (iii) are further confirmed by our results presented below. Conversely, production of the − :CO 2 H intermediate, measured indirectly as HCO 2 − (formate), has been investigated here for the first time to our knowledge.…”
Section: Significancesupporting
confidence: 87%
See 1 more Smart Citation
“…S2), HydG variants lacking a functional second cluster are expected to produce − :CO 2 H-derived formate instead of CO and water. Points (i)-(iii) have already been addressed (11)(12)(13)26) and (ii) and (iii) are further confirmed by our results presented below. Conversely, production of the − :CO 2 H intermediate, measured indirectly as HCO 2 − (formate), has been investigated here for the first time to our knowledge.…”
Section: Significancesupporting
confidence: 87%
“…Δ CTD = mutant with a C-terminal domain deletion (III). Its tyrosine binding affinity at I is reduced (26). + and -signs signify increased and diminished production, respectively (or consumption in the case of tyrosine).…”
Section: Significancementioning
confidence: 99%
“…Conversely, these mutations completely abolish CO synthesis, indicating that this process requires the second [Fe 4 S 4 ] cluster (Fig. 2, A and C) (27,28). We concluded that, although CO and CN Ϫ are produced at similar rates (12,13), their syntheses are not simultaneous and are likely to occur at different locations of the protein (27,28).…”
Section: Activity Of [Fefe]-hydrogenase Maturasesmentioning
confidence: 81%
“…These studies show that the C-terminal stretch that coordinates the second [Fe 4 S 4 ] cluster forms a domain that interacts extensively with the bottom of the TIM barrel (Fig. 2B) (28). The truncation mutant is still capable of cleaving tyrosine to produce p-cresol (28).…”
Section: Activity Of [Fefe]-hydrogenase Maturasesmentioning
confidence: 95%
See 1 more Smart Citation